Operation of Lumbar Zygoapophyseal Joint Cysts Using a Full-Endoscopic Interlaminar and Transforaminal Approach: Prospective 2-Year Results of 74 Patients. (December 2014) - Komp, Martin; Hahn, Patrick; Ozdemir, Semih; Merk, Harry; Kasch, Richard; Godolias, Georgios; Ruetten, Sebastian
In appropriate situations, extensive decompression with laminectomy often continues to be described as the method of choice for operations involving lumbar zygoapophyseal joint (z-joint) cysts. Tissue-sparing procedures are nevertheless becoming more common. Endoscopic techniques have become the standard procedures in many areas because of the advantages they offer in terms of surgical technique and in rehabilitation. One key aspect in spinal surgery was the development of instruments for sufficient bone resection carried out under continuous visual control. This enabled endoscopes to be used when operating on z-joint cysts. The objective of this prospective study was to examine the technical possibilities for the full-endoscopic interlaminar and transforaminal technique in lumbar z-joint cysts. A total of 74 patients were followed up for 2 years. The results show that 85% of the patients no longer have any leg pain or that the pain had been almost completely eliminated, and 11 % experience occasional pain. The complication rate was low. The full-endoscopic techniques brought advantages in the following areas: operation, complications, traumatization, and rehabilitation. The recorded results show that full-endoscopic resection of a z-joint cyst using an interlaminar and transforaminal approach provides an adequate and safe supplement, and is an alternative to conventional procedures when the indication criteria are fulfilled. It also offers the advantages of a minimally invasive intervention.